Byron's Lost American Library. Issue 1 (June 2017) - Accardo, Peter X.
Abstract : An unpublished presentation letter from George Ticknor in the John Murray Archive at the National Library of Scotland provides evidence that five American imprints, including Washington Irving's A History of New York, were sent to Byron in September 1815. While no corroborative evidence survives that Byron ever received them, the books gain interest in their connection to Ticknor as an arbiter of American letters and in what they might have revealed in Byron as a champion of American culture.